Sleep quality and sleep hygiene in Slovenian university students during the COVID-19 pandemic - Vita Štukovnik; Marina Horvat; Vesna Vrečko Pizzulin; Leja Dolenc Grošelj (Zdravniški Vestnik)
Background: The COVID-19 pandemic has profoundly impacted global physical and mental health. This study sought to 1) assess Slovenian university students’ sleep habits during the initial COVID-19 epidemic and lockdown and 2) evaluate sleep hygiene’s role as a potential predictor of sleep quality during this period.